2018
DOI: 10.1002/jum.14588
|View full text |Cite
|
Sign up to set email alerts
|

A Review and Proposed Rationale for the use of Ultrasonography as a Diagnostic Modality in the Identification of Bone Stress Injuries

Abstract: Bone stress injuries are common in military personnel and athletes. The delayed diagnosis of a bone stress injury can lead to a more severe injury that requires a longer period of treatment. The early detection of bone stress injuries is a central part of management. Currently, the reference standard for detecting bone stress injuries is magnetic resonance imaging. However, the expanding use of point-of-care ultrasonography (US) may enable the early detection of bone stress injuries in the clinical setting. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 71 publications
0
17
1
Order By: Relevance
“…8,11,[35][36][37] Our study confirmed acromial pathology with ultrasonography, which is a valuable tool in detecting non-displaced fractures, occult cortical fractures, and periosteal reactions that cannot be confirmed by plain radiography. 28,29,32,36,38 Thus, the acromial pathology incidence was higher in our study than in previous reports. Moreover, according to previous studies, the causes of acromial fracture include osteoporosis, ACJ arthritis, acromion morphology and thickness, diabetes, nutritional status, and bone quality.…”
Section: Discussioncontrasting
confidence: 65%
“…8,11,[35][36][37] Our study confirmed acromial pathology with ultrasonography, which is a valuable tool in detecting non-displaced fractures, occult cortical fractures, and periosteal reactions that cannot be confirmed by plain radiography. 28,29,32,36,38 Thus, the acromial pathology incidence was higher in our study than in previous reports. Moreover, according to previous studies, the causes of acromial fracture include osteoporosis, ACJ arthritis, acromion morphology and thickness, diabetes, nutritional status, and bone quality.…”
Section: Discussioncontrasting
confidence: 65%
“…56 Early tibial BSI may be detected on fat-saturated T2 and STIR images with bone marrow or periosteal edema as well as cortical abnormalities. 57 Kijowski and colleagues defined several MRI features of tibial BSI: periosteal edema, linear high T2 signal immediately adjacent to the outer cortex; bone marrow edema, low T1 and high T2 within the canal; cortical abnormality (Table 1). 39 MRI may be useful in evaluating other causes of leg pain in athletes, such as chronic exertional compartment syndrome and peripheral neuropathy.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…77 It has the ability to identify presence of hypoechoic calluses and buckling in the bony cortex more than other imaging modalities. 57 Diagnostic ultrasound has a sensitivity of 43-99% and specificity of 13-79%. 27 The sensitivity of MSK US for identifying BSI on the posterior cortex of the tibia is low.…”
Section: Musculoskeletal Ultrasoundmentioning
confidence: 99%
“…Overuse injuries (bone fractures, musculoskeletal injuries), occurring when involved structures fail to adapt to increased mechanical stress [1][2][3][4][5], mostly affect resistance athletes, athletes involved in pre-season preparation, and military populations [3,[5][6][7][8][9][10][11][12][13][14][15]. In the army, most injuries occur both during the training of new recruits and in special training contexts (incidence up to �7% for men and 21% for women [16]) [3,10,11,13,[15][16][17]. The implications in terms of patient morbidity, recurrence, reduced military performance, and dropout rates do represent a relevant public health problem and a demand for efficient surveillance, prevention and treatment plans [3,11,15].…”
Section: Introductionmentioning
confidence: 99%